Perancangan Interior Kapal Pesiar yang dapat Mengenalkan Pariwisata di Kota Luwuk-Sulawasi Tengah - Chandra, Sugiarto Raharjo (Intra, 2013)
Yacht interior design in the city Luwuk aims to generate and introduce tourism Luwuk city area, and provide for visitor learning how to care for and preserve the existing biodiversity in the city Luwuk, particularly the endangered endemic animals.The methods used to achieve these objectives, the object survey design, data collection library that can support the design, collection of data obtained, and the method of analysis, the method of analysis used is by comparing interior yacht in Indonesia and abroad, to get a comparison of facilities and the need for reference in designing the interior of a cruise ship, the field survey carried out by the method of directly observing objects design conditions and interviews with the crew.To give a tropical feel to the interior of the vessel widley applied use of materials combined whit wood carving motifs taken from tradirtional clothes, as for how to imtroduce the richness of the city Luwuk using education space where visitors will get a wealth of information about Luwuk.